Downregulation of the Host Gene jigr1 by miR-92 Is Essential for Neuroblast Self-Renewal in Drosophila. - Yuva-Aydemir, Y.; Xu, X.L.; Aydemir, O.; Gascon, E.; Sayin, S.; Zhou, W.; Hong, Y.; Gao, F.B. (PLoS Genetics, 2015)
Intragenic microRNAs (miRNAs), located mostly in the introns of protein-coding genes, are often co-expressed with their host mRNAs. However, their functional interaction in development is largely unknown. Here we show that in Drosophila, miR-92a and miR-92b are embedded in the intron and 3'UTR of jigr1, respectively, and co-expressed with some jigr1 isoforms. miR-92a and miR-92b are highly expressed in neuroblasts of larval brain where Jigr1 expression is low. Genetic deletion of both miR-92a and miR-92b demonstrates an essential cell-autonomous role for these miRNAs in maintaining neuroblast self-renewal through inhibiting premature differentiation. We also show that miR-92a and miR-92b directly target jigr1 in vivo and that some phenotypes due to the absence of these miRNAs are partially rescued by reducing the level of jigr1. These results reveal a novel function of the miR-92 family in Drosophila neuroblasts and provide another example that local negative feedback regulation of host genes by intragenic miRNAs is essential for animal development.